Purification of total IgG from sars-cov-2 convalescent serum - Arfat Lusinanto; Ria Syafitri Evi Gantini; Dwirini Retno Gunarti; Mohamad Sadikin (Acta Biochimica Indonesiana, 2025)
Background: Although convalescent plasma contains neutralizing anti-SARS-CoV-2 antibodies, co-existing inflammatory mediators pose safety risks in critically ill recipients. Purified IgG preparations offer a safer alternative by concentrating therapeutic antibodies while eliminating these harmful components. Objective: To establish a systematic protocol for purifying total IgG from SARS-CoV-2 convalescent serum using sequential chromatographic techniques. Methods: Serum from 90 RT-PCR-confirmed recovered donors was pooled into three independent samples. Purification employed four sequential steps: ammonium sulfate precipitation (50% saturation), Sephadex G-100 size-exclusion chromatography, DEAE-Cellulose ion-exchange chromatography, and Protein A affinity chromatography. Purity and identity of IgG fractions were assessed by native polyacrylamide gel electrophoresis and radial immunodiffusion. Results: Starting from serum containing 19.68 ± 7.27 mg/mL IgG and 110.47 ± 11.99 mg/mL total protein, the four-step purification yielded a final IgG concentration of 1.14 ± 0.70 mg/mL with total protein of 1.19 ± 0.16 mg/mL, representing 6.3-fold purification with a final IgG-to-total protein purity ratio of 1.01 ± 0.38 and an overall recovery of 5.8%. Native PAGE confirmed high purity with a single dominant IgG band. Conclusion: Sequential chromatography yielded near-homogeneous IgG from SARS-CoV-2 convalescent serum, offering a laboratory-scale approach for preparing safer immunoglobulin therapeutics.